Presentation Ideals in Locally Multiplications Modules - Jabbar, Adil Kadir (Sulaimani Journal for Pure and Applied Sciences, 2014)
In this paper, presentation ideals in locally multiplication modules are studied. It is known that if is a multiplication module and are submodules of , then and, for ideals of and the product , is defined as . We generalize this concept to locally multiplication modules and we prove that under certain conditions some results that concerning presentation ideals in multiplication modules can be generalized to locally multiplication modules.
Keywords: presentation ideal; multiplication module; locally multiplication module; Primal,weakly prime; weakly prime